Needs, Rights and "One Law for All": Contemporary Debates in New Zealand Maori Politics - O'Sullivan, Dominic (Canadian Journal of Political Science / Revue canadienne de science politique, 2008)
This paper examines contemporary debates in Maori politics by responding to the argument of the former leader of the opposition National party, Don Brash, that Maori public policy is most properly based on "need" alone because indigenous status offers no "rights" beyond those of common national citizenship. The paper's alternative argument is that the politics of indigeneity and associated theories of self-determination provide a way of avoiding a general belief that addressing need is all that is required to include Maori fairly in the national polity. It is argued that Maori ought to enjoy rights of indigeneity as the basis of an inclusive, cohesive and fair society. /// Cette étude examine certains débats dans le domaine de la politique maorie en répondant aux propos de l'ancien chef du parti National, Don Brash, selon qui la politique publique maorie se baserait le plus aptement sur la notion du seul 'besoin', le statut de peuple indigène ne conférant aucun 'droit' au-delà de ceux qu'accorde la citoyennenté nationale régulière. Nous proposons par contre que la politique de l'indigénéité et les théories de l'auto-détermination qui y sont associées constituent un moyen de parer à une croyance généralisée qu'il suffirait de suppléer au besoin pour inclure avec justice les Maoris dans la politique nationale. Nous démontrerons que dans une société inclusive, cohésive et juste, les Maoris devraient jouir des droits accordés par l'indigénéité.
Keywords: māori rights; protest; racism; ōrewa speech

The Treaty of Waitangi in Contemporary New Zealand Politics - O'Sullivan, Dominic (Australian Journal of Political Science, 2008)
This paper identifies three discourses that are prominent in contemporary Treaty of Waitangi policy debate, each with significantly different implications for Maori political status within the modern nation-state. At one extreme the Treaty's significance is exaggerated by overemphasis on partnership as an implicit Treaty principle. At another extreme the Treaty's significance is understated by an assimilationist position that denies the Treaty's relevance to Indigenous rights which, in turn, imposes serious constraint on the extent to which partnership can actually develop into comprehensive policy practice. An alternative position is one that sees the Treaty, which is supported in international law, as affirming a twofold conception of citizenship as the basis of both individual and collective Maori rights.
Keywords: māori rights; partnership; tiriti o waitangi/treaty of waitangi; treaty obligations